Missed nursing care, level of staffing, and job satisfaction - Doumit, Myrna (2013)
Missed nursing care refers to omission of standard required nursing care of patients in acute care hospitals. The objective of this study was to compare the amounts and reasons of missed nursing care, the level of nurse staffing, and job satisfaction between the United States and Lebanon. Several studies in the United States have shown that a significant amount of care is being missed. This study is designed to determine if Lebanon is experiencing a similar phenomenon and what reasons are given for missing nursing care. Findings support that a substantial amount of nursing care is missed in Lebanon, although less than that in the United States (t = 11.53, P < .001), that nurses in Lebanon were less satisfied with being a nurse than are nurses in the United States, and there was no difference in the identification of staffing resources as a reason for missed care in the 2 countries.